New Year Lecture 2021 by Prof. Dr. Ute Fendler (2021)
Prof. Ute Fendler delivers her Lecture on "Polyrhythmic gestures - Relational Perspectives on/from verbal, audio/visual and performative arts across the African continent". It was held on 14 January 2021 as the first academic event of the Cluster of Excellence in the new year. The Cluster’s spokesperson Prof. Dr. Ute Fendler engaged with the key term of relationality by combining concepts from Glissant’s poetics of relation as well as from Deleuze’s polyrhythm, Benítez Rojo’s concept of "chaos" and Brathwaite’s "tidalectics". All of them suggest ways of approaching multiple and complex ways of being in the world. The lecture put them in dialogue with concepts suggested by Senghor on "rhythm" in the new readings by Bachir Diagne and also by Babacar M. Diop. Furthermore, Ute Fendler drew on Vilem Flusser’s "gestures" as symbolic gestures to discuss some examples from verbal, visual and performative art works that allow us to navigate the entanglements between theory and practice, like e.g. poem/songs by Raharimanana (Madagascar), music/films by Moussa Sène Absa (Senegal), and dance/calligraphy. The lecture had been planned as a dialogic lecture with artists, but due to the pandemic, the whole event had to be recorded beforehand. Prof. Fendler: "I would like to thank Mr. Makhoukh who accepted to give an interview on his work and his thoughts on the key concepts “polyrhythm” and “relationality”. I would also like to thank Dr. Driss ElMaarouf who did the interview in Fes and also Farouk ElMaarouf who did the postproduction and the subtitles. Furthermore, I would like to thank Raharimanan for sharing the link to the concert that can be seen on vimeo and of which I showed a part as he could not come to Bayreuth." The video of the dance-calligraphy is a short part of the video on the site: https://www.streamsandmountains.com/the-calligraphy-of-dance Link to Raharimanan's poem: https://vimeo.com/208144946